Community pharmacist's perspective regarding patient-centred communication in conjunction with pharmaceutical practice: A cross-sectional survey - Aura Rusu; Marius Călin Chereches; Cristian Popa; Raluca Botezatu; Ioana-Andreea Lungu; Octavia-Laura Moldovan (Elsevier, 2022)
Effective communication between pharmacists and patients is essential for therapeutic success. The pharmacist's perspective may differ from that of the patient in terms of effective communication. Our study aimed to assess the communication efficiency in the pharmacist-patient relationship from the pharmacists' perspective. We hypothesize that the community pharmacist's perspective can lead to relevant aspects of patient-centred communication and their profession. A cross-sectional study was conducted through an online questionnaire addressed to pharmacists. A number of 506 questionnaires were collected, evaluated, analyzed and interpreted. The questionnaire focused on the following main issues: degree of job satisfaction, essential skills of a pharmacist working in a community pharmacy, different aspects of pharmacist-patient communication, shared decision-making, patient monitoring plan and other elements related to a patient under treatment (healthy lifestyle, receptivity to counselling, loyalty and appreciation of pharmaceutical services). The pharmacist's efficiency in communication with the patient and professional education were also targeted in the study. There are no significant differences between job satisfaction in women compared to men. However, the job satisfaction increases with the average age. Caregiver, communicator and life-long learner were identified as essential skills of a pharmacist. Pharmacists participating in the study generally perceive themselves as good communicators with the patient. Nevertheless, many particular aspects of communication with patients can be greatly improved. The lack of training in the spirit of the "patient-centred communication" concept has been identified. Still, more than a third of the respondents are missing the need for professional training. A periodic evaluation of the efficiency of pharmacist-patient communication in the community pharmacy is necessary. The degree of subjectivity of the pharmacist from this perspective and self-sufficiency would be significantly diminished if the pharmacists had access to the results of the periodic evaluations.